Earthquake Processes: Physical Modelling, Numerical Simulation and Data Analysis Part II 2002
DOI: 10.1007/978-3-0348-8197-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Critical Sensitivity and Trans-scale Fluctuations in Catastrophic Rupture

Abstract: -Rupture in the heterogeneous crust appears to be a catastrophe transition. Catastrophic rupture sensitively depends on the details of heterogeneity and stress transfer on multiple scales. These are difficult to identify and deal with. As a result, the threshold of earthquake-like rupture presents uncertainty. This may be the root of the difficulty of earthquake prediction. Based on a coupled pattern mapping model, we represent critical sensitivity and trans-scale fluctuations associated with catastrophic rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2003
2003
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Critical sensitivity means that a system may become sensitive significantly as approaching its catastrophe transition point. The underlying mechanism behind critical sensitivity is the coupling effect between disordered heterogeneity on multiple scales and dynamical nonlinearity due to damage-induced stress redistribution (STEIN, 1999;XIA et al, 2000XIA et al, , 2002WEI, et al 2000). Critical sensitivity may provide a clue to the prediction of catastrophe transition, such as material failure and great earthquakes, provided the sensitivity of the system is measurable or can be monitored.…”
Section: Introductionmentioning
confidence: 99%
“…Critical sensitivity means that a system may become sensitive significantly as approaching its catastrophe transition point. The underlying mechanism behind critical sensitivity is the coupling effect between disordered heterogeneity on multiple scales and dynamical nonlinearity due to damage-induced stress redistribution (STEIN, 1999;XIA et al, 2000XIA et al, , 2002WEI, et al 2000). Critical sensitivity may provide a clue to the prediction of catastrophe transition, such as material failure and great earthquakes, provided the sensitivity of the system is measurable or can be monitored.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the LURR decreases to a low level before the large event occurs. XIA et al, (2002) presented critical sensitivity to describe the damage evolved in materials. The numerical simulation of the damage and fracture process for brittle inhomogeneous material also shows a peak of sensitivity prior to the catastrophic rupture which is similar to the variation of LURR (ZHANG et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The critical point hypothesis for large earthquakes predicts two different precursory phenomena in space and time, an accelerating moment release and the growth of the spatial correlation length between its different parts. XIA et al (2002) presented critical sensitivity and trans-scale fluctuations associated with catastrophic rupture in a system. Critical sensitivity means that the system becomes significantly sensitive near the catastrophe transition.…”
Section: Introductionmentioning
confidence: 99%
“…The catastrophe transition occurring in such media is the most important feature in this problem (BAI et al, 1994;XIA et al, 2002;WEI et al, 2000). In rock mechanics (JAEGER and COOK, 1979), it is found that at the beginning of loading, micro-damages appear on mesoscopic heterogeneities.…”
Section: Introductionmentioning
confidence: 99%